2018
DOI: 10.3390/ijerph15112355
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Distribution of Particulate Phosphorus and Their Correlation with Environmental Factors in a Shallow Eutrophic Chinese Lake (Lake Taihu)

Abstract: Spatial and seasonal variations of particulate phosphorus (PP) in a large shallow, eutrophic Lake Taihu with different ecotypes (including a phytoplankton-dominated zone, lake center zone, estuary zone and macrophyte-dominated zone) were investigated. The results showed that particulate organic phosphorus (POP) was the dominant form of PP (>88.0%). The concentration of POP showed higher levels in the bloom-sensitive northwestern zone (phytoplankton-dominated zone and estuary zone) during warm seasons, phytopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 40 publications
(42 reference statements)
0
8
0
Order By: Relevance
“…The adsorption and release characteristics of sediments change with the contents of the overlying water, physicochemical properties of sediments [17,18], water temperature (T W ) [19], dissolved oxygen (DO) [20], pondus hydrogenii (pH) conditions [21], and other environmental factors [22,23]. For reservoirs in the monsoon climate zone, environmental and water quality indicators vary with seasonal changes, which cause the adsorption and release characteristics of the sediments to change seasonally.…”
Section: Introductionmentioning
confidence: 99%
“…The adsorption and release characteristics of sediments change with the contents of the overlying water, physicochemical properties of sediments [17,18], water temperature (T W ) [19], dissolved oxygen (DO) [20], pondus hydrogenii (pH) conditions [21], and other environmental factors [22,23]. For reservoirs in the monsoon climate zone, environmental and water quality indicators vary with seasonal changes, which cause the adsorption and release characteristics of the sediments to change seasonally.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, enclosure culture in East Taihu Bay (the region Site 5 located) reached its peak from 1998 to 2008 (Wang et al 2019). Although suffered a mass of anthropogenic organic matter inputs, the water quality of East Taihu Bay was better than that of algae-dominated zone (Kong et al 2018). It seems that the large area of submerged macrophytes and floating-leaf macrophytes play important role in maintain water quality and favorable food web structure.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies indicated that Pyro-P was a degradation product of Poly-P under the action of microbial metabolism; Poly-P and Pyro-P are both potential bioavailable phosphorus, which are actively involved in the P circulation in water and are closely related to the nutrient level of lakes. [18,45].…”
Section: Discussionmentioning
confidence: 99%
“…A large number of microorganisms can be attracted or reproduced on the surface of PPOM to carry out strong bio-metabolic activities [16,17]. The more easily decomposed PPOM can rapidly degrade through a series of redox and phosphatase hydrolysis processes, releasing various species of P to the surrounding water body [18]. Part of P entering the water body is dissolved in water and can be directly absorbed and utilized by algae and other organisms [19]; part of P enters the sediment with the deposition of particulate matter and then suspends under the disturbance of wind, waves, and organisms, re-entering the overlying water body and participating in the P cycle [20].…”
Section: Introductionmentioning
confidence: 99%